2022
DOI: 10.7759/cureus.22070
|View full text |Cite
|
Sign up to set email alerts
|

Rare Adverse Events Related to Nivolumab, an Immune Checkpoint Inhibitor: A Case Series

Abstract: Immune checkpoint inhibitors are a novel class of immunotherapy drugs that have improved the prognosis of melanoma, renal cell carcinoma, non-small cell lung cancer, urothelial carcinoma, and various other solid tumors. Nivolumab is an immune checkpoint inhibitor that acts by inhibiting programmed death. Its use is associated with significant immune-related adverse events, such as pneumonitis, thyroiditis, hepatitis, pruritus, vitiligo, and diarrhea. However, adrenal insufficiency and checkpoint inhibitor-rela… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Several studies have suggested [ 10 , 12 , 13 ] that PD-1 and PD-L1 immune checkpoint inhibitors can cause adrenal insufficiency, which can be categorized as primary or secondary pituitary inflammation. Clinical symptoms of adrenal insufficiency include fatigue, nausea, and weakness.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies have suggested [ 10 , 12 , 13 ] that PD-1 and PD-L1 immune checkpoint inhibitors can cause adrenal insufficiency, which can be categorized as primary or secondary pituitary inflammation. Clinical symptoms of adrenal insufficiency include fatigue, nausea, and weakness.…”
Section: Discussionmentioning
confidence: 99%
“…During immunotherapy, irAEs in the endocrine system are common [ 12 ]. However, pituitary inflammation is relatively rare, especially in patients treated with PD-1 or PD-L1 alone [ 18 , 19 ].…”
Section: Discussionmentioning
confidence: 99%